THE USE OF LRD (Listen-Read-Discuss) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION OF THE SECOND GRADE STUDENTS AT SMP N.2 TEMBILAHAN - Purwanti, Sri Erma (Fakultas Keguruan dan Ilmu Pendidikan, Program Studi Pendidikan Bahasa Inggris, 2017)
The aim of this research is to find out the effectiveness of using LRD Strategy in improving students’ reading comprehension of the second-grade students at SMPN.2 Tembilahan. LRD strategy is a literacy strategy that builds students’ prior knowledge before they read a text. It is a powerful tool for engaging struggling readers in classroom discussion. There were two classes taken by the researcher, experimental group, and control group. The treatment was given to the experimental group for eight meetings. The materials were Recount text and Descriptive Text. The instrument used was multiple choices test consisting of 30 questions. By the end of the meeting, the researcher gave them post-test. The result of the analysis shows that the LRD strategy significantly improves the students’ reading comprehension.